Is Real-World Price a Tale Told by the Idiot of Chance? - Samuelson, Paul A. (The Review of Economics and Statistics, 1976)
Kendall, M. G., and A. Stuart, Advanced Theory of Statistics, Vol. 2 (London: Charles Griffin, 1961). Labys, W. C., and C. W. J. Granger, Speculation, hledging and Price Forecasts (Lexington, Mass.: Heath Lexington, 1970). Samuelson, P. A., Proof that Properly Anticipated Prices Fluctuate Randomly, Industrial Mana-gement Review, 6 (Spr. 1965), 41-49. Stevenson, R. A., and R. M. Bear, Commodity Futures: Trends or Random Walks?, Journal of Finance, XXV (Mar. 1970), 65-81. Telser, L. G., The Supply of Speculative Services in Wheat, Corn and Soybeans, Food Research Institute Studies, VII, Supplement (1967), 131-176.